An ethnobotanical inventory and therapeutic potential of medicinal plants used in traditional practices in northeastern Algeria - Aouir , Fatima; Chaibi , Rachid; Benhamza , Abd El Hakim; Benchettouh , Ahmed; Gouzi , Hicham; Benaceur , Farouk; Chenchouni, Haroun (Ethnobotany Research and Applications, 2025)
Background: Medicinal plants are a precious heritage and a true wealth of humanity and are highly sought after all over the world, especially in developing countries where poorest communities need it to treat various diseases. Objective: This floristic and ethnobotanical study was carried out with the aim of carrying out the most complete inventory possible of medicinal plants and gathering as much information as possible concerning the therapeutic practices practiced in the region of Setif, northeastern Algeria. Methods: Using a semi-structured questionnaire and based on a simple stratified random approach, 250 selected local residents were directly interviewed. The collected data were examined using quantitative indices of ethnobotany. Results: A total of 109 plant species belonging to 42 different families were recorded. Of these, the Asteraceae were the most represented with 15 taxa, followed by the Lamiaceae with 13 species. The analysis of relationships between medicinal species and the types of diseases treated showed that the plants commonly used were Cuminum cyminum L., Vicia faba L., Mentha spicata L., Olea europaea subsp. europaea L., Citrus aurantium L., Citrus limon (L.) Burm.f, and Aloysia citrodora Paláu, which were the most widespread in the area. Most of these taxa were used mainly in the care of the digestive system (19.75%) and metabolic disorders (14.88%) by the infusion of the leaves which represents the most dominant preparation recipe among the local population. Conclusion: The ethnobotanical results obtained not only provide a very valuable source of information on the medicinal flora of the study area, but also show that it is possible to use certain plants in socio-economic development, particularly in Algerian rural areas. Keywords: Ethnobotanical study, Medicinal plant, Traditional medicine, Therapeutic uses, Algeria.